PEMANFAATAN PENGOLAHAN CITRA UNTUK VEGETASI DAN LAHAN DI AREA RAWAN LONGSOR - Ridho’i, Ahmad; Sutriono, Bantot (Jurnal Leverage, Engagement, Empowerment of Community (LeECOM), 2020)
Indonesia is a country which is part of its territory as an area with a row of fire ring, which is vulnerable to disasters. Disasters can be in the form of volcanic eruptions, earthquakes, floods, landslides, and so on. Landslides generally occur on sloped land which is certainly present in the mountains, and landslides can be triggered by a number of uses of land that are not in accordance with their function, deforested land, water flow from altitude to poor valleys. The occurrence of a landslide disaster leaves or causes several problems in the affected area which can be in the form of the land itself or for humans in the affected land, due to a landslide disaster resulting in productive crops being damaged, affected land changing conditions or changing the boundaries of land ownership the. Landslides need to be monitored or monitored by the area before and after a landslide event to determine the affected plants and land, making it easier to identify and ensure losses experienced by those who inhabit the affected area. Determination of areas affected by both productive plants, affected land can be done using image processing, image processing can estimate what percentage of plants and lands affected by landslides.